TRACTOR TRAILER: A REVIEW OF PAPERS FROM THE SCOPUS DATABASE PUBLISHED IN ENGLISH FOR THE PERIOD OF 2000-2022 - Baynazarov, Hayrullo (Научно-технический журнал «Машиностроение», 2024)
This study aims to provide an extensive opportunity to review the published literature on trailer construction. The research includes general information about the world's leading scientists and journals.